2021
DOI: 10.1001/jama.2021.1195
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Central Nervous System–Active Polypharmacy Among Older Adults With Dementia in the US

Abstract: IMPORTANCE Community-dwelling older adults with dementia have a high prevalence of psychotropic and opioid use. In these patients, central nervous system (CNS)-active polypharmacy may increase the risk for impaired cognition, fall-related injury, and death.OBJECTIVE To determine the extent of CNS-active polypharmacy among community-dwelling older adults with dementia in the US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 42 publications
(79 reference statements)
5
64
1
Order By: Relevance
“…Medication lists reflect both continued or newly prescribed medications at each sampled outpatient visit, and it is not possible to determine longitudinal changes or decisions to discontinue medications. Finally, our measure of polypharmacy included both regular and as‐needed medications, which cannot be distinguished in NAMCS; this could have led to an overestimation of actual medication exposure, which may be better captured using other data sources 19 . Despite these potential limitations, NAMCS has been used historically in many studies 20,27,28 to provide national estimates of outpatient prescribing practices in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Medication lists reflect both continued or newly prescribed medications at each sampled outpatient visit, and it is not possible to determine longitudinal changes or decisions to discontinue medications. Finally, our measure of polypharmacy included both regular and as‐needed medications, which cannot be distinguished in NAMCS; this could have led to an overestimation of actual medication exposure, which may be better captured using other data sources 19 . Despite these potential limitations, NAMCS has been used historically in many studies 20,27,28 to provide national estimates of outpatient prescribing practices in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Such prescribing of antidepressants is part of the common polypharmacy seen in people with dementia in the community. 22 Mirtazapine, a noradrenergic and specific serotonergic antidepressant, is widely used in older people; from 2009 to 2014, in a study of 4•8 million antidepressant initiations in Europe, it was the antidepressant most commonly prescribed for older people and those with dementia. 23 We examined it as a treatment for depression in dementia in the HTASADD trial and found no evidence of efficacy for depression.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…However, some recent reviews presented a more tempered perspective on AEs of nonbenzodiazepines receptor agonists, noting that over a quarter-century of use and tens of millions of doses taken in elderly people may imply that short-term use at appropriate dosing may be suitable in some cases [114]. Recent analyses of prescriptions derived from both commercial [115] and Medicare [116] databases suggested historical trends towards lower usage of zolpidem and the other "z-drugs" for sleep, suggesting a strong influence of the Beers criteria and existing observational studies in clinical practice.…”
Section: Benzodiazepines/site-specific Gamma-aminobutyric Acid Agonistsmentioning
confidence: 99%
“…Dosing of agents needs to be further clarified, especially in the AD population, where a narrow therapeutic window already exists because of concomitant medications, medical pathology, and compromised physiological reserves. Among community-dwelling Medicare recipients with dementia using multiple psychotropics, the most commonly used psychoactive medications included gabapentin, trazodone, and quetiapine [116], and much of the dosing was nocturnal, potentially to induce and/or maintain sleep. None of these medications have been subject to adequate clinical trial testing as hypnotics.…”
Section: Limitationsmentioning
confidence: 99%